2004
DOI: 10.1038/sj.mp.4001385
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan for loci of Asperger syndrome

Abstract: Asperger syndrome (AS), characterised by inadequate social interaction, lack of empathy and a dependence of routines and rituals, is classified as belonging to the autism spectrum disorders (DSM-IV and ICD-10). Although the prevalence of AS has been estimated to range from 0.3 up to 48.4 per 10 000, the phenotype still remains relatively unrecognised by clinicians. Several reports, including the original description by Hans Asperger (1944), have suggested that AS has a strong genetic component. Here, we have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 52 publications
3
54
1
6
Order By: Relevance
“…Several research groups have performed full genome screens in AD. 40,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] Research groups, study design and main findings of linkage studies that reported positive results are summarized in Table 1 for genome-wide linkage and association studies with a qualitative AD phenotype, and in Table 2 for linkage studies with either a quantitative phenotype, a specific qualitative endophenotype, or other specific linkage models. 122,123,127,130,[138][139][140][141][142][143][144][145][146][147][148] From Table 1, it can be seen that linkage has been found in at least two independent studies in regions 2q, 3q25-27, 3p25, 6q14-21, 7q31-36 and 17q11-21.…”
Section: Linkage Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have performed full genome screens in AD. 40,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] Research groups, study design and main findings of linkage studies that reported positive results are summarized in Table 1 for genome-wide linkage and association studies with a qualitative AD phenotype, and in Table 2 for linkage studies with either a quantitative phenotype, a specific qualitative endophenotype, or other specific linkage models. 122,123,127,130,[138][139][140][141][142][143][144][145][146][147][148] From Table 1, it can be seen that linkage has been found in at least two independent studies in regions 2q, 3q25-27, 3p25, 6q14-21, 7q31-36 and 17q11-21.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…120,125,131,132 A recent heterogeneity-based genome search metaanalysis 150 again supported region 7q22-q32, which reached genomewide significance in studies on strictly defined autism, and revealed two loci of suggestive significance (10p12-q11.1;17p11.2-q12) in studies on AD and the BAP. Nine linkage studies 119,120,123,126,[131][132][133]136,151 were included in this meta-analysis. Between-scan heterogeneity was low for the locus on 7q, but high for the loci on 10p 12-q11.1 and 17p11.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…Third, twin and family studies have provided compelling evidence for a strong genetic component among autistic individuals (Folstein et al, 2003;Hu-Lince et al, 2005;Vorstman et al, 2006). Multiple genome-wide screens have found evidence for linkage to autism in several chromosomes, including chromosomes 2, 6, 7, 15, 17, 20 and X (International Molecular Genetic Study of Autism Consortium (IMGSAC), 1998, 2001); Barrett et al, 1999;Philippe et al, 1999;Risch et al, 1999;Collaborative Linkage Study of Autism, 2001;Buxbaum et al, 2001;Ylisaukko-oja et al, 2004;Hu-Lince et al, 2005). Likewise, analysis of reported cytogenetic abnormalities (i.e.…”
Section: Wnt Signaling and Autismmentioning
confidence: 99%
“…A number of such scans has been published in the last decade 9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and many of them have been recently updated, expanded, or elaborated in twostage designs in an effort to generate additional information for specific promising chromosomal regions. Despite some overlap in the findings of these scans, typically each scan has shown little or no evidence for strong linkage signals and the results are generally difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%